Effect of La doping on ZnO thin films by spray pyrolysis - Nassiba Allag; Leila Segueni; Chahnez Said; Boubaker Benhaoua; Djamel Barani; Brahim Gasmi (University of Eloued, 2019)
Zinc oxide (ZnO) undoped and Lanthanum doped (ZnO: La) thin films were deposited on 400°C heated glass using spray pyrolysis technique with moving nozzle . (Zn (CH3COO)2, 2H2O) and (LaCl3, 7H2O) were used as sources of ZnO and Lanthanum respectively. Effects of dopant on the optical, structural and opto-electrical properties of undoped and 2,4,6 wt. % Lanthanum doped ZnO thin films .Optical transmittance spectra of the films showed high transparency of about 98% in visible region. The optical gap,for ZnO and 0,2,4wt. % La doped ZnO thin films ,were found to be in 3.25-3.28 eV range . X-ray diffraction showed that the thin films have hexagonal wurtzite structure with a strong (002) as preferred orientation, whereas the crystalline size was ranged in 15.89-33.45 nm.. ZnO thin films are promising to be used a light emitting diodes ,gas sensor and UV detectors
Intervention
Keywords: Zinc Oxide; thin films; XRD; La doped; Uv-visible. Introduction